Characteristic Compounds Identification and Authenticity Evaluation of Heptapleurum Honey - Qiqi WANG; Zhonglian HUANG; Li WANG; Jie DONG; Xun LIN; Gensheng ZHANG (Shipin gongye ke-ji, 2023)
In order to clarify the characteristic compounds and establish the authenticity evaluation method of heptapleurum honey, high-performance liquid chromatography coupled with quadrupole-time-of-flight tandem mass spectrometry (HPLC-Q/TOF-MS/MS) was used to qualitative and quantitative analysis of characteristic compounds in heptapleurum honey. Five compounds were identified including 4-(1'-cyclodiethyl ether-3'-butanediol)-3,5,5-trimethyl-2-cyclohexenone (Unedone B), 3,4,5-trimethoxy cinnamyl alcohol, 4-(1'2'-dihydroxy-3'epoxypropane) -3,5,5-2-cyclohexenone (Unedone C), trans, trans abscisic acid, and cis, trans abscisic acid. Notably, 3,4,5-trimethoxy cinnamyl alcohol was first found in honey, and it could be a marker of heptapleurum honey. Moreover, 10 raw heptapleurum honey samples with different geographic origins were collected to establish HPLC fingerprint. The authenticity of six commercial heptapleurum honey samples were evaluated by combining characteristic compound with HPLC fingerprint. The results demonstrated that three brands of sample were genuine pure heptapleurum honey, two brands of sample might be mixed with other honeys. A brand sample did not contain characteristic compound and were significantly different with the standard fingerprints of heptapleurum honey. It was inferred that the sample was not heptapleurum honey. This study provides theoretical reference for the authenticity evaluation of heptapleurum honey.